2020
DOI: 10.1371/journal.pone.0237792
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency variation near common germline susceptibility loci are associated with risk of Ewing sarcoma

Abstract: Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…However, it remains unclear whether these factors contribute to incidence trends that we observed in older age groups, and few other extrinsic factors have been associated with this disease 9,26,27,31 . More recent analyses indicate that germline genetic susceptibility contributes substantially to ES development and may be a stronger risk factor than locally varying extrinsic factors 32‐34 . However, changes to the frequency of genetic risk variants within a population are unlikely to have occurred during a 25‐year timespan.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it remains unclear whether these factors contribute to incidence trends that we observed in older age groups, and few other extrinsic factors have been associated with this disease 9,26,27,31 . More recent analyses indicate that germline genetic susceptibility contributes substantially to ES development and may be a stronger risk factor than locally varying extrinsic factors 32‐34 . However, changes to the frequency of genetic risk variants within a population are unlikely to have occurred during a 25‐year timespan.…”
Section: Discussionmentioning
confidence: 86%
“…9,26,27,31 More recent analyses indicate that germline genetic susceptibility contributes substantially to ES development and may be a stronger risk factor than locally varying extrinsic factors. [32][33][34] However, changes to the frequency of genetic risk variants within a population are unlikely to have occurred during a 25-year timespan. Therefore, the possibility that at least some of the trends we observed in ES incidence are a consequence of changing case detection and recognition over time merits consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the pathogenesis of ES is essential for identifying new biomarkers to develop new therapeutic strategies [12,13]. However, metastasis and recurrence are the main causes of poor prognosis of ES [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, first-degree relatives of patients with EwS have an increased risk of developing cancers such as brain and female genital cancers, and second-degree relatives demonstrated an increased risk of breast cancer among others 102 . Genome-wide association studies have identified genetic haplotypes associated with an increased risk of EwS 103 , 104 , which possibly contribute to disease onset through generating higher affinity binding sites for EWSR1::FLI1 as shown at EGR2 cis-regulatory elements 105 , 106 .…”
Section: Summary Of Evidence For Molecular Biomarkers For Risk-strati...mentioning
confidence: 99%